Globalization, new regionalization, restructuring, and NAFTA implications for the signatories and the Caribbean. - WATSON, Hilbourne A. (1996)
Views NAFTA as a concrete aspect of the economic, political, and cultural changes transpiring in the world today. Points out that the new regionalization is a process that is rooted in globalization. Examines the reasons why NAFTA is of real concern to CBI countries.